Color: measurement systems and their importance in the food industry - Magda Valdes Restrepo; Johannes Delgado Ospina; Liliana Londoño-Hernández; Robert Augusto Rodríguez Restrepo (Temas Agrarios, 2023)
Color is one of the main characteristics that allows to establish the quality of food. Technically, it is defined as a mental response to the stimulus that a visible radiation produces in the retina that is transmitted to the brain by the optic nerve, so it is closely related to the nervous system and thus, this attribute in food marks the preference of an individual. Given its importance, different systems have been developed to objectively measure color in food, evaluating the changes obtained in a product due to processing and storage, determining, among other things, its shelf life. Considering the above, this review is presented with the objective of recognizing the main methods for determining color of food, and its applications in the food industry.